2021
DOI: 10.1111/vco.12675
|View full text |Cite
|
Sign up to set email alerts
|

Determining agreement between preoperative computed tomography lymphography and indocyanine green near infrared fluorescence intraoperative imaging for sentinel lymph node mapping in dogs with oral tumours

Abstract: Lymphatic drainage from the head and neck is variable with significant crossover, therefore sentinel lymph node (SLN) mapping can help ensure the appropriate lymph node(s) are sampled. To improve sensitivity, SLN mapping utilizing multiple modalities and a combination of preoperative computed tomography lymphography (CTL) and intraoperative near infrared fluorescence imaging (NIRF) with indocyanine green (ICG) +/− methylene blue (MB) dye has been suggested. The aim of this study was to describe a method for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 46 publications
5
49
1
Order By: Relevance
“…While debate exists regarding the optimal technique for sentinel LN mapping, the use of dual methods (dye and advanced imaging) has been suggested to optimize sentinel LN detection. 12,29,30 However, in routine clinical practice, LN mapping is often restricted to methylene blue dye, mainly due to logistic issues related to radioisotopes, technical challenges and financial constraint.…”
Section: Discussionmentioning
confidence: 99%
“…While debate exists regarding the optimal technique for sentinel LN mapping, the use of dual methods (dye and advanced imaging) has been suggested to optimize sentinel LN detection. 12,29,30 However, in routine clinical practice, LN mapping is often restricted to methylene blue dye, mainly due to logistic issues related to radioisotopes, technical challenges and financial constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Using special camera devices with a light spectrum between 650 and 850 nm, the near-infrared fluorescent dye is lightening up the lymphatics to a tissue depth of 1 cm and displays the SLN on a screen in real time. Near-infrared fluorescent SLN mapping in dogs with oral malignancies was recently published by Wan et al (2021). However, there is currently no controlled clinical study available that documents the actual value of near-infrared fluorescent image-based LNDs in dogs affected by MCTs.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study performed in dogs with oral neoplasia recently underlined the superior performance of ICG to methylene blue and CT lymphography. 25 Applications in cats have so far not been published. This case has shown that NIR-L is easy to perform in a cat and two clear lymphograms could be generated.…”
Section: Discussionmentioning
confidence: 99%